Communication in a wired world be smart, be safe - Schrank, Louise Welsh; Stage Fright Productions; Learning Seed Company (Chicago, Illinois : Learning Seed, 2009)
Documentary exploring skills for communicating smartly across many digital technologies. Focuses on how multitasking affects learning and work, and how online posts can create skeletons in a digital closet, causing school expulsions, destroying college admissions, and blowing job offers. Viewers will learn how to protect their privacy, reputation and personal information
Title from title screen
Host: Olivia Porter
DVD Format
With English subtitle
Keywords: Information technology -- Social aspects; Information technology -- Security measures; Information society; Privacy, Right of; Computer security